Ecotourism,livelihood System and Decoupling Sustainabilty in Wakatobi, Southeast Sulawesi - ., Kasmiati; Dharmawan, Arya Hadi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTThis study was conducted in Wakatobi Southeast Sulawesi Province. Wakatobi overall administrative region is a national park established by decree of the Ministry Forestry No.7651/KPTS-II/2002 dated August 19 Wakatobi National 2002. Wakatobi National Park was the second largest marine park was owned by Indonesia and became one of the national tourism destination. It was the latest Indonesian biosphere reserves established by UNESCO in the 24th session of the ICC-MAB program in 2012, Paris.Wakatobi geostrategic position in the center of the world’s coral led to an area that has a very rich biodiversity and have the beautifully and exotic underwater scenery. The superiority of location (geographical advantage) being the reason for local governments to establish ecotourism as a paradigm of Wakatobi regional development. This study examines the livelihood systems and the level of household resilience after ecotourism developed in Wakatobi through “Sustainable Livelihood Aproach”.In this study, it can be concluded that the development of ecotourism in the region has not given more contribution thus hamper the achievement of regional development based on ecotourism as nature conservation was maintained and well-being of local communities. However, the development of ecotourism still was inclusive so that people who are able to access such availability was top class household groups. Ecotourism basically can increase the economic resilience of households.Keywords: regional development, ecotourism, livilihood, resilience, decoupling sustainabilityABSTRAKPenelitian ini dilaksanakan di Kabupaten Wakatobi Provinsi Sulawesi Tenggara. Secara keseluruhan wilayah adminstrasi Wakatobi merupakan taman nasional yang ditetapkan berdasarkan surat keputusan Menteri Kehutanan No.7651/KPTS-II/2002 tanggal 19 Agustus tahun 2002.Taman Nasional Wakatobi merupakan taman laut terbesar kedua yang di miliki Indonesia dan menjadi salah satu Daerah Tujuan Wisata nasional. Merupakan cagar Biosfer terbaru Indonesia yang ditetapkan oleh UNESCO melalui sidang ke-24 ICC-MAB program pada tahun 2012 di Paris. Posisi Geostrategis Wakatobi di tengah pusat karang dunia, menyebabkan daerah ini sebagai wilayah yang memiliki keanekaragamn hayati yang sangat tinggi dan mempunyai pemandangan alam bawah laut yang indah dan eksotik. Keunggulan lokasi (geographical advantage) menjadi alasan Pemerintah Daerah menetapkan Ekowisata sebagai paradigma pembangunan wilayah Wakatobi. Penelitian ini bertujuan melihat sistem penghidupan dan tingkat resiliensi rumahtangga setelah ekowista dikembangkan di Wakatobi menggunakan pendekatan “Sustainable Livelihood aproach”. Hasil kesimpulan penelitian ini adalah kegiatan ekowisata belum berkontribusi besar dalam pembangunan wilayah karena terjadi persoalan ”Decoupling Sustainability”, hal ini menghambat tercapainya tujuan pembangunan wilayah yang berbasiskan ekowisata yaitu kelesetarian alam terjaga dan masyarakat lokal memperoleh manfaat. Tetapi yang terjadi adalah pembangunan ekowisata yang belum inklusif sehingga hanya lapisan rumahtangga atas yang mampu mengakses peluang yang tersedia. Ekowisata pada dasarnya dapat meningkatkan resiliensi ekonomi rumahtangga.Kata kunci: pembangunan wilayah, ekowisata, livelihood , resiliensi, decoupling sustainabiliti